What Happened to Transitional Justice in Croatia After the EU Accession? - Strupinskienė, Lina; Vaškevičiūtė, Simona (Politologija, 2021)
This paper proposes to see Croatia’s becoming a member state of the European Union in 2013 as a particular critical juncture that created uncertainty over the type of decisions the government would take in the field of transitional justice once international pressure had stopped. It compares the period before and after the accession by looking into the three elements of transitional justice policy that were given priority by the EU conditionality framework – fighting impunity for war crimes, fostering reconciliation and respect for and protection of minority rights. It finds that all three have deteriorated in the post-accession period. On the one hand, the findings illustrate the power of international pressure, but on the other hand, they question the overall effectiveness of the conditionality policy, as it seems to not have affected deeper societal issues at stake and has not resulted in true transformation.
Keywords: Croatia; Transitional Justice; Human Rights; European Union